KEGIATAN PEMANFAATAN TEKNOLOGI DIGITAL UNTUK PROMOSI DAN PENGEMBANGAN UMKM DESA BREBEK WARU SIDOARJO - Muhammad Yusron Maulana El-Yunusi; Mirza Elmy Safira; Zidni Akholik Almaghfiroh; Nadia Wulidar Rohmah (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy; however, they continue to face various challenges, particularly in the utilization of digital technology for marketing and business development. Most MSME actors in Brebek Village, Waru District, Sidoarjo Regency still rely on traditional marketing methods, resulting in limited competitiveness and market reach. This community service activity aimed to empower MSME actors through the utilization of digital technology to enhance business promotion, competitiveness, and income. The method employed was the Asset-Based Community Development (ABCD) approach, which emphasizes the utilization of local assets and community potential. The activity was conducted over two days and included observation, interviews, digital literacy education, and mentoring on the creation of promotional content using the Canva application, as well as the utilization of social media platforms such as Instagram and WhatsApp. The results indicate an improvement in the understanding and skills of MSME actors in using digital technology for business promotion. MSME participants were able to independently create promotional posters and began utilizing social media to reach a wider market. This activity had a positive impact on increasing business visibility and the potential for increased MSME sales. Nevertheless, limitations related to time, devices, and internet access remain challenges that need to be addressed in future implementations. Overall, this activity contributes to enhancing the digital readiness of MSMEs and supports the strengthening of the local economy in Brebek Village.